Respiratory immunisation and mucosal immunity against influenza - Martini, V (2022)
Influenza A virus (IAV) is a considerable threat to human and animal health. Current immunisation strategies rely primarily on inducing strain-specific neutralising antibodies with a limited breadth of protection. Increasing evidence indicates the importance of local immune responses and tissue resident memory T cells (TRM) for broad protection against respiratory infections, however, a vaccine that can be safely delivered to the lung is yet to be approved. In addition, there is little information on influenza A virus (IAV) specific TRM in the pig, a large animal model for IAV research, and a natural reservoir for the virus.